A review on recent advances in cold plasma technology for the food industry: Current applications and future trends. (November 2017) - Chizoba Ekezie, Flora-Glad; Sun, Da-Wen; Cheng, Jun-Hu
Abstract: Background: Cold plasma (CP) is an emerging technology, which has attracted the attention of scientists globally. It was originally developed for ameliorating the printing and adhesion properties of polymers plus a variety of usage domains in electronics. In the last decade, its applications were extended into the food industry as a powerful tool for non-thermal processing, with diverse forms for utilization. Scope and approach: This review presents an overview of recent studies on the application of cold plasma in the food industry. Specific areas discussed include microbial decontamination of food products, packaging material processing, functionality modification of food materials and dissipation of agrochemical residues. The application of CP has also been expanded into areas, such as hydrogenation of edible oils, mitigation of food allergy, inactivation of anti-nutritional factors, tailoring of seed germination performance and effluent management. In addition, the paper provides a summary of plasma chemistry and sources, factors influencing plasma efficiency and strategies for augmentation. Furthermore, key areas for future research are highlighted and salient drawbacks are discussed. Key findings and conclusions: The recent studies conducted on the interaction of reactive species with food contact surfaces establish plasma processing as an eco-friendly technique with minimal changes to food products, making it a befitting alternative to traditional techniques. Active researches focused on up-scaling for commercial applications are urgently required. Highlights: Cold plasma technology has continued to gain positive ratings in the food industry. Interaction of reactive species with food materials minimally affects quality parameters. New pathways for their utilization during food processing were highlighted. Future research pathways to facilitate their recognition were proposed.